The middle of somewhere - Cheaney, J. B. (Knopf, 2007)
Twelve-year-old Ronnie loves organization, especially because her brother has attention-deficit hyperactivity disorder, but traveling with their grandfather who is investigating wind power in Kansas brings some pleasant, if chaotic, surprises.